P180 Endoscopic scoring systems for Crohn's Disease and Ulcerative Colitis and their correlation with histological and clinical outcomes. (27th May 2021) - Gibbons, E; Hayes, T; Shahzad, C K; Hussain, A; Hall, B; Smyth, C; Farrell, R; Kelly, O
Abstract: Background: Endoscopy and histopathology are vital for evaluating disease activity and treatment response in inflammatory bowel disease. Correlation between endoscopic and histological indices has not been fully examined. The primary aim of this study was to examine the correlation of endoscopic scores with histological assessment and association with flare/hospitalisation in the ensuing 12 months. Methods: We selected 100 random colonoscopies performed for IBD surveillance/assessment in 2019. Adult patients with a complete colonoscopy were included. All reports were blindly scored by 2 expert endoscopists using SES CD or Mayo score as appropriate. Histology was retrieved from HistoLab database and classified as normal, mild, moderate and severe. Clinical demographics, CRP, fecal calprotectin levels, flare episodes and hospitalisations were recorded. Correlation between endoscopic and histologic activity was tested. Comparisons were made between patients in histologic and endoscopic remission v those with endoscopic and histologic activity regarding association with flare/hospitalisation. Results: 100 IBD patients (median age 49 IQR 22; 54% female; 50% Crohn's disease) were included. A wide range of SES-CD scores were noted (median score 2 and IQR 6). 48% were in remission (0–2), 34% mild with score 3–6, 18% moderate with score 7–15 and 4% severe disease activity scoring > 16. Of those in endoscopic remission, 87.5% had normal histology. Of the 9 with moderate endoscopic disease all ranges of histological status were described. All levels of the Mayo scale (median score 1) were represented. Similar to the Crohn's group, 87.5% of those in endoscopic remission also had normal histology. In total 42 patients were in both endoscopic and histological remission, and only 7% experienced a flare of disease activity in the following 12 months, with no hospitalisations. In total 40 patients had both endoscopically and histologically active disease, and 45% of these had a flare in the ensuing 12 months with two hospitalisations.The ROC curve for SES-CD score and histological remission is 0.73 +/- 0.07 95%CI 0.59 -0.87 and for the Mayo score and histological remission 0.87 +/- 0.05 95%CI 0.78- 0.97. Conclusion: Accurate assessment of disease activity guides therapy choices and helps assess response to treatment in our IBD cohort. In this study the SES-CD and Mayo endoscopic scores showed good correlation with histological assessment. Those with active endoscopic and histologic disease experienced more flares and had higher rates of hospitalisation than those in remission. Further investigation with higher study numbers and incorporation of a standardised histological grading system are required.